THU0279 Weight Loss after Total Knee Arthroplasty in the Rheumatoid Arthritis Patient. (10th June 2014) - Zuckerman, T.; Datta, K.; Broder, A.
Abstract : Background: Whether restored mobility bestowed by Total Knee Arthroplasty (TKA) facilitates weight loss in rheumatoid arthritis (RA) patients has not been studied specifically [1] RA patients may face barriers to post-operative weight loss, such as corticosteroid use and upper extremity arthritis limiting rehabilitation [2] Clinicians need to counsel RA patients regarding expectations for weight loss after TKA. Objectives: To determine if significant weight loss occurred in overweight and obese RA patients 6-18 months after TKA compared to non-RA patients Methods: All TKAs done at Montefiore Medical Center from 2001-2012 were identified in the electronic medical record. The RA group was defined as patients with at least 2 visits with International Classification of Diseases, Ninth Revision (ICD9) code 714.0 for rheumatoid arthritis and a prescription for ≥1 disease modifying anti-rheumatic drug [3]. The non-RA group was defined as those without RA (714.0), spondyloarthritis (720.x, 696.1, 099.3), inflammatory bowel disease (555.x), or connective tissue disease (710.x). Peri-operative (30 days before to 7 days after) and post-operative (6-18 months after) weight (kg) and body mass index (BMI) (kg/m 2 ) was obtained. Overweight (BMI ≥25-29.9) and obese (BMI ≥30.0) patients were included in the analysis [4]. Bivariate analysis compared baseline characteristics (demographics, Charlson comorbidity index [5]) and post-operative weight changes of RA and non-RA groups. Multivariate analysis adjusted for gender, ethnicity, race, and comorbidity index. Weight change of >±5% was considered clinically significant [6]. Results: Using defined criteria, 46 RA and 1348 non-RA patients were identified. Of these, 14 (30%) RA and 331 (25%) non-RA were overweight; 31 (67%) RA and 894 (66%) non-RA were obese, p<0.218 . Peri-operatively, RA patients were younger, with mean age of 60±10 years, compared to non-RA, 65±10, p<0.002 . There was no difference in gender or comorbidity score between the groups. Post-operatively, 20% of RA patients and 20% of non-RA patients lost >5% of their peri-operative body weight, p<0.811. However, 24% of RA and 14% of non-RA gained >5% body weight, p<0.039. In a logistic regression model, age was a predictor of weight gain, p<0.044 . Conclusions: A small minority of RA patients lost significant weight 6-18 months after TKA. In contrast, more RA patients gained significant weight, compared to non-RA patients. This data apprises clinicians who counsel RA patients regarding weight loss after TKA. Future studies can identify factors associated with significant weight change. References: Stets K, et al. Weight and body mass index change after total joint arthroplasty. Orthopedics. 2010 Jun 9;33(6):386. Danoff JR, et al. Total Knee Arthroplasty Considerations in Rheumatoid Arthritis. Autoimmune Dis. 2013;2013:185340. Kim SY, et al. Validation of rheumatoid arthritis diagnoses in health care utilization data. Arthritis Res Ther. 2011 Feb 23;13(1):R32. Centers for Disease Control and Prevention. Overweight and obesity: defining overweight and obesity. http://www.cdc.gov/nccdphp/dnpa/obesity/defining.htm . Charlson M, et al. Validation of a combined comorbidity index. J Clin Epidemiol. 1994 Nov;47(11):1245-51. Overweight, obesity, and health risk. National Task Force on the Prevention and Treatment of Obesity. Arch Intern Med. 2000; 160(7):898-904. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.3935